What We Know about the Impact of School and Scouting on Adolescents' Value-based Leadership - Émiliane Rubat du Mérac (LED Edizioni Universitarie, 2015)
The purpose of this study is to understand the impact of the school environment compared to the Scouting environment on the leadership attitudes of adolescents. The ways in which the social context affects the development of leadership attitudes is of special importance in view of the guidelines issued by the OECD, UNESCO and European Union, which envision schools as places of social development. In order to examine the ways in which these different contexts affect leadership development, we used two instruments: the «Educational Context Perception Questionnaire» (ECPQ), for the analysis of the adolescents' perception of their educational context, and the «Socially Responsible Leadership Scale» (SRLS), which measures the Individual, Group, and Social Values of the adolescents, to which we added a dimension of Leadership Capacities. The study was conducted on a judgment sample, consisting of 600 students and 231 Scouts enrolled in upper secondary school in Rome (9th and 10th grades). Path-analyses were conducted to test, for the students and the Scouts, the effects of the ECPQ dimensions on leadership attitudes and capacities and to determine the relationships between the leadership dimensions. Findings revealed different effects among students and Scouts, of the educational context perception on their leadership attitudes and capacities, an effect of the Individual Values on the Group Values and an effect of the Group Values on the Social Values and Leadership Capacities.